Diversity of the Germination Apparatus in Clostridium botulinum Groups I, II, III, and IV - Brunt, Jason; van Vliet, Arnoud H. M.; van den Bos, Fédor; Carter, Andrew T.; Peck, Michael W. (Frontiers in Microbiology, 2016)
Clostridium botulinum is a highly dangerous pathogen that forms very resistant endospores that are ubiquitous in the environment, and which, under favourable conditions germinate to produce vegetative cells that multiply and form the exceptionally potent botulinum neurotoxin. To improve the control of botulinum neurotoxin-forming clostridia, it is important to understand the mechanisms involved in spore germination. Here we present models for spore germination in C. botulinum based on comparative genomics analyses, with C. botulinum Groups I and III sharing similar pathways, which differ from those proposed for C. botulinum Groups II and IV. All spores germinate in response to amino acids interacting with a germinant receptor, with four types of germinant receptor identified (encoded by various combinations of gerA, gerB and gerC genes (gerX)). There are three gene clusters with an ABC-like configuration; ABC [gerX1], ABABCB [gerX2] and ACxBBB [gerX4], and a single CA-B [gerX3] gene cluster. Subtypes have been identified for most germinant receptors types, and the individual GerX subunits of each cluster show similar grouping in phylogenetic trees. C. botulinum Group I contained the largest variety of gerX subtypes, with three gerX1, three gerX2 and one gerX3 subtypes, while C. botulinum Group III contained two gerX1 types and one gerX4. C. botulinum Groups II and IV contained a single germinant receptor, gerX3 and gerX1, respectively. It is likely that all four C. botulinum Groups include a SpoVA channel involved in DPA release. The cortex lytic enzymes present in C. botulinum Groups I and III appear to be CwlJ and SleB, while in C. botulinum Groups II and IV, SleC appears to be important.